The Computer Misuse Act 1990: Lessons from its Past and Predictions for its Future. . - MacEwan, Neil (Criminal Law Review, 2008)
The age of the internet has thrown down some real challenges to the Computer Misuse Act 1990. Recently, the Government made changes to this piece of legislation, in an attempt to meet two of those challenges--the proliferation of "Denial of Service" (DOS.) attacks, and the creation and dissemination of "Hackers" tools"--and to fulfil international commitments on cybercrime. Yet some of these new measures invite criticisms of policy, form and content, and bring doubts about how easy to interpret, and how enforceable, they will be.